The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.890188
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Emulsion Gels as Functional Colloids Emphasizing Food Applications: A Review

Abstract: Gels are functional materials with well-defined structures (three-dimensional networks) assembled from the dispersed colloids, and capable of containing a large amount of water, oil, or air (by replacing the liquid within the gel pores), known as a hydrogel, oleogel, and aerogel, respectively. An emulsion gel is a gelled matrix filled with emulsion dispersion in which at least one phase, either continuous phase or dispersed phase forms spatial networks leading to the formation of a semisolid texture. Recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 114 publications
(144 reference statements)
0
18
0
Order By: Relevance
“…The PEG did not had the noticeable affect on MUFA content of the semi-smoked sausages, probably due to the higher amount of MUFA in horsemeat (40.1%) compare to beef or pork [ 40 ]. Horsemeat is low in fat and has a high concentration of healthy omega-3 polyunsaturated fatty acids (PUFA), including linolenic (18:3n-3) and other long-chain n-3 fatty acids (FA), which have been shown the valuable effect to prevent some chronic diseases [ 1 , 3 , 4 , 6 , 7 ]. The ω-6/ω-3 ratio describes how healthier is meat products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PEG did not had the noticeable affect on MUFA content of the semi-smoked sausages, probably due to the higher amount of MUFA in horsemeat (40.1%) compare to beef or pork [ 40 ]. Horsemeat is low in fat and has a high concentration of healthy omega-3 polyunsaturated fatty acids (PUFA), including linolenic (18:3n-3) and other long-chain n-3 fatty acids (FA), which have been shown the valuable effect to prevent some chronic diseases [ 1 , 3 , 4 , 6 , 7 ]. The ω-6/ω-3 ratio describes how healthier is meat products.…”
Section: Resultsmentioning
confidence: 99%
“…In order to meet the growing demand for horsemeat, attempts have been made to improve the horsemeat’s sustainability and safety. Emulsification technology could be used to improve the quality of semi-smoked sausages made from horsemeat by helping to increase their viscosity and stability, as well as control the moisture of the product [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 indicates several intelligent packaging systems such as gas, pH, time, temperature, and humidity sensors, being incorporated into or printed onto the food packaging materials in order to monitor the real time quality of the packaged food ( 84 ). In recent years, studies have also reported the development of biosensors being employed for the detection of pathogenic bacteria ( 85 , 86 ).…”
Section: Classification Of Filmsmentioning
confidence: 99%
“…Owing to their dual character of solid/fluid behavior, especially the viscoelastic aspect, they are widely seen in nature, and popular in industrial applications including food products. [1][2][3] A special class of these materials are organogels wherein gelation is caused by low molecular weight gelators (LMWGs). The guided self-assembly in these systems is controlled by weak forces, such as van der Waals, hydrogen bonding, electrostatic forces, p-p stacking, and London dispersion forces.…”
Section: Introductionmentioning
confidence: 99%